Pembuatan Video Animasi sebagai Media Literasi Terhadap Bahaya Judi Online - Zidan Dwi Fatwa Aulia; Feliza Zubair; Rinda Aunillah Sirait (BADAN PENERBIT STIEPARI PRESS, 2025)
The animated video titled Digital Threats: The Dangers of Online Gambling was created to educate the public about the risks, impacts, and potential solutions related to online gambling. This project was motivated by the rising value of online gambling transactions in Indonesia, which continues to increase each year. The animation is designed in a 2D format using the keyframing method. The purpose of this writing is to explain the production process behind the creation of the animated video, which involves three main stages: pre-production (including story ideation, scriptwriting, visual design, and storyboarding), production (voice-over recording and animation development), and post-production (audio editing and final rendering). The final product is a 4-minute and 37-second 2D animated video that delivers informative content on the harmful effects of online gambling, as well as preventive and practical solutions for those trapped in gambling addiction. The video is designed to be accessible to a wide audience through engaging visuals and easy-to-understand narratives. In conclusion, this work demonstrates that 2D animation is an effective medium for conveying complex educational messages in a simplified and engaging manner. This project is expected to serve as an alternative digital educational tool that supports digital literacy campaigns and raises awareness about the dangers of online gambling in society.